Polymer-nanoclay mixed matrix membranes for CO2/CH4 separation: A review - Jamil, A. (Trans Tech Publications Ltd, 2014)
Mixed matrix membrane (MMM) has shown significant progress towards gas separation. Rigid polymers are suitable materials for MMM fabrication but adhesion problems with filler need to be addressed. A variety of inorganic fillers have been studied for CO2 separation but clay minerals were not considered much in this class. The layered silicate structure of nanoclay such as montmorillonite provides excellent opportunity to manipulate its properties, leading towards better dispersion and adhesion towards the polymer matrix. This paper reviews the potential of polymernanoclay MMM for CO2/CH4 separation. Â© 2014 Trans Tech Publications, Switzerland.